(untitled) (International Journal of Biology and Chemistry, 2015)
Natural Killer (NK) cells are known to lyse tumor cells lacking MHC-I and expressing ligands for activating receptors, thereby participating in cancer immune surveillance. However, their function and phenotype change significantly in cancer patients. The precise molecular mechanism(s) involved in this phenomenon remain unknown. The aim of the present study was to investigate changes of both receptor phenotype and cytotoxic activity of NK cells cocultured with K562 and HepG2 cells in dual-chamber Transwell® plates. A decrease of NK cell cytotoxicity against K562 cells was demonstrated. This effect was not a result of changes in perforin, granzyme or CD107a expression by NK cells or by production of cytokines (IFNγ, TNFα, IL-10, and TGFβ). No changes in the expression of a majority of NK cell receptors (CD16, CD69, 2B4, NKG2A, NKG2D, NKp30, NKp44, NKp46, and DNAM1) were observed. Only an increase in the percentage of NK cells bearing inhibitory receptor TIGIT was found as a result of co-culture with tumor cells. Possible molecular mechanisms of altered NK cell cytotoxicity involving TIGIT are discussed.